2014
DOI: 10.1186/bcr3609
|View full text |Cite
|
Sign up to set email alerts
|

Nonhypoxic regulation and role of hypoxia-inducible factor 1 in aromatase inhibitor resistant breast cancer

Abstract: IntroductionAlthough aromatase inhibitors (AIs; for example, letrozole) are highly effective in treating estrogen receptor positive (ER+) breast cancer, a significant percentage of patients either do not respond to AIs or become resistant to them. Previous studies suggest that acquired resistance to AIs involves a switch from dependence on ER signaling to dependence on growth factor-mediated pathways, such as human epidermal growth factor receptor-2 (HER2). However, the role of HER2, and the identity of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…Activation of the PI3K/Akt pathway inhibits cell apoptosis by mediating the endogenous expression of Bcl-2 and Bax, which are mediators of apoptosis and are are the most frequently targeted genes regulating apoptosis in cells (36). In addition, activation of the PI3K/Akt pathway reduces the expression levels of P-gp, BCRP, MRP1 and other members of the ABC transporter superfamily (37)(38)(39)(40). These two aspects of the PI3K/Akt pathway, at least in part, induce the development of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the PI3K/Akt pathway inhibits cell apoptosis by mediating the endogenous expression of Bcl-2 and Bax, which are mediators of apoptosis and are are the most frequently targeted genes regulating apoptosis in cells (36). In addition, activation of the PI3K/Akt pathway reduces the expression levels of P-gp, BCRP, MRP1 and other members of the ABC transporter superfamily (37)(38)(39)(40). These two aspects of the PI3K/Akt pathway, at least in part, induce the development of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In SW480 cells glucose consumption was higher at 10% than at 1% oxygen. Because the studies were conducted for 120 hours, observed effect may be related with attenuated HIF‐1 activity in chronic hypoxia . Differently, metastatic SW620 cells used similar amount of glucose at 1% and 10% oxygen possibly due to their better adaptation to oxygen variability.…”
Section: Discussionmentioning
confidence: 99%
“…While hypoxia increases HIF-1α protein stability and specific transcriptional activity [124], heregulin/HER2 signaling induces synthesis of HIF-1α protein, such that a combination of hypoxia and HER2 overexpression synergistically increases HIF-1α target genes expression [110]. Normoxic expression of HIF-1α was reported to mediate HER2 effects on resistance to aromatase inhibitors in breast cancer cells [125]. Aromatase inhibitors reduce circulating levels of estrogen and are clinically used to treat breast cancer [126].…”
Section: Erbb Family Receptorsmentioning
confidence: 99%
“…In particular, breast cancer resistant protein (BCRP), a HIF-1α target gene, was reported to play a role in resistance to these agents and in maintenance of stem cell characteristics in breast cancer. Hence, inhibition of HIF-1α expression and activity has been suggested to extend tumor cells sensitivity to aromatase inhibitors and averting recurrence and metastasis [125].…”
Section: Erbb Family Receptorsmentioning
confidence: 99%